The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fneur.2020.00817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Repetitive Transcranial Magnetic Stimulation on Neurocognition and Oxidative Stress in Relapsing-Remitting Multiple Sclerosis: A Case Report

Abstract: Multiple sclerosis (MS) is a neurodegenerative condition whose manifestation and clinical evolution can present themselves in very different ways. Analogously, its treatment has to be personalized and the patient's response may be idiosyncratic. At this moment there is no cure for it, in addition to its clinical course sometimes being torpid, with a poor response to any treatment. However, Transcranial Magnetic Stimulation (TMS) has demonstrated its usefulness as a non-invasive therapeutic tool for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Therefore, the search for new treatments is particularly important, and TMS is an additional way to treat MS. TMS has outstanding features compared with the existing drug treatment methods in many aspects, especially with fewer side effects. What is more, its safety has been confirmed by many related studies (16,27). Thus, TMS is thought to be a promising new method for the treatment of MS.…”
Section: Treatment Of Tms In Msmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, the search for new treatments is particularly important, and TMS is an additional way to treat MS. TMS has outstanding features compared with the existing drug treatment methods in many aspects, especially with fewer side effects. What is more, its safety has been confirmed by many related studies (16,27). Thus, TMS is thought to be a promising new method for the treatment of MS.…”
Section: Treatment Of Tms In Msmentioning
confidence: 89%
“…At the same time, it can inhibit the apoptosis pathway of mitochondria, reduce the apoptosis of nerve cells, and play a neuroprotective role ( 41 ). Aguera et al presented the case of a woman diagnosed with MS more than a decade earlier and who was not responding to conventional medications ( 27 ). In view of this, they decided to try a treatment with rTMS for 1 year.…”
Section: Treatment Of Tms In Msmentioning
confidence: 99%
“…Agüera et al ( 141 ) reported a case of RRMS (33 years, female) not responding to medications prescribed over 9 years and rapidly progressing disease. The patient benefited from rTMS which was prescribed as a compassionate treatment as no other treatment was producing any benefit.…”
Section: Tms In Multiple Sclerosismentioning
confidence: 99%
“…The patient benefited from rTMS which was prescribed as a compassionate treatment as no other treatment was producing any benefit. Post rTMS, there was improvement in her neuropsychological functions and blood tests showed a reduction in oxidative stress after 4 months of treatment ( 141 ).…”
Section: Tms In Multiple Sclerosismentioning
confidence: 99%
“…Interestingly, rTMS display its anti-oxidative effects in multiple brain diseases [ 223 , 224 ]. For example, multiple sclerosis patients who received long-term treatment with 1-Hz rTMS showed significant improvement in various levels of psychometric evaluation and blood analysis [ 225 ]. Notably, there is a marked reduction of oxidative stress in the plasma [ 225 ].…”
Section: Introductionmentioning
confidence: 99%